Sound feedback control model for live electronic performance in the Ecos Study - Thomasi, Ricardo; Faria, Regis R. A. (Revista Vórtex, 2021)
Through the Ecos Study we investigate possibilities for musical structuring based on theories of emergence, finding a fertile territory for experimentations within Agostino Di Scipio’s paradigm of Audible Ecosystems. The inclusion of the acoustic environment as an active component of the musical system led us to rethink classical techniques of sound synthesis and modelling, some traditional models of electroacoustic performance, and to criticize the very role of interactions in a qualitative perspective. A positive feedback control model has been developed aiming at understanding the behaviour and the structure of the ecosystem supporting the implementation of the Spatial Instrument, a core element implemented through MAX/MSP patch and that offers a logical rationale for organizing speakers and microphones in the acoustic space. We introduce the underlying theoretical debate and present the feedback control mechanism as the basis from which the Spatial Instrument is developed.